Macroalgal species composition and diversity in Northwestern Leyte, Philippines - Bancale, Maruja Jessa B.; Payo, Dioli Ann O. (2016)
Macroalgal studies have been conducted all throughout the Philippines as reflected in the works of both Filipino and foreign psychologists. However, the macroalgal flora of Northwestern Leyte coastal waters remains understudied. This study evaluated the different species of macroalgae and the macroalgal species diversity patterns present in the towns of Merida, Isabel, and Palompon. The areas were sampled between November 2015 and January 2016 using random and quadrat sampling. A total of 44 taxa were identified including 18 species of Chlorophyta, 14 species of Rhodophyta, and 12 species of Phaeophyta. Palompon had the highest mean percent cover of 60.62 plus or minus 0.77 seaweed species, followed by Merida with a percent cover of 58.40 plus or minus 0.40, and Isabel with a percent cover of 49.90 plus or minus 0.28. Isabel had the highest diversity with 27 species, Merida had 25 species, and Palompon had the lowest diversity with 21 species. Among the species identified, Halimeda opuntia was the most abundant in all of the sites. In this study, 21 macroalgal species were identified which were not previously reported by Silva et al. in 1987. This study provides a baseline biodiversity data for future--more complex biomonitoring studies and exploration of the potentials of locally available seaweeds. The result may also be used for formulating and implementing guidelines for coastal management and conservation of marine algal resources in the area.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Science and technology